(untitled) (Al-Aasar, 2026)
This study examined how gender, age, and education shape the relationship between identity struggles and life satisfaction among internally displaced persons (IDPs) from Waziristan. Using a cross-sectional correlational design, 250 IDPs recruited through snowball sampling completed standardized measures: The In-Group Identification Scale, and Satisfaction with Life Scale, along with demographic information. Correlation and group-comparison analyses (IBM SPSS, version 22) revealed that stronger in-group identification (fewer identity struggles) was associated with higher life satisfaction. The important demographics trends appeared, including that women have reported considerably fewer identity struggle and higher life satisfaction as compared to men, although with higher identity struggles, younger IDPs, paradoxically, demonstrated higher life satisfaction than older groups and education turned out as the strongest protective factor, with highly educated persons demonstrating greater in-group identification and life satisfaction as compared to those with no formal education. These findings indicate the need for demographically informed psychosocial interventions from the relative authorities and a society as a whole.